Mitochondrial dysfunction induced by fatty acid ethyl esters, myocardial metabolites of ethanol. - Lange, L G (1983)
Mechanisms responsible for alcohol-induced heart muscle disease have been difficult to elucidate partly because of previously obscure, demonstrable cardiac metabolism of ethanol. Recently, fatty acid ethyl esters were identified in our laboratory and found to be myocardial metabolites of ethanol. In the present study, they have been shown to induce mitochondrial dysfunction. Incubation of isolated myocardial mitochondria with fatty acid ethyl esters led to a concentration-dependent reduction of the respiratory control ratio index of coupling of oxidative phosphorylation and decrement of maximal rate of oxygen consumption. Furthermore, fatty acid ethyl esters were demonstrated to bind to mitochondria in vitro, and, importantly, 72% of intracellularly synthesized ethyl esters were found to bind to mitochondria isolated from intact tissue incubated with ethanol. Protein binding of fatty acid ethyl esters was markedly less than that of fatty acids. Because uncoupling of mitochondrial oxidative phosphorylation correlated with the cleavage of fatty acid ethyl ester shown to be initially bound to mitochondria, with resultant generation of fatty acid, a potent uncoupler, in a locus in or near the mitochondrial membrane, fatty acid ethyl esters may contribute to a potentially toxic shuttle for fatty acid with transport from physiological intracellular binding sites to the mitochondrial membrane; direct effects of fatty acid ethyl esters may also be deleterious. Operation of this shuttle as a result of ethanol ingestion and subsequent accumulation of fatty acid ethyl esters may account for the impaired mitochondrial function and inefficient energy production associated with toxic effects of ethanol on the heart.